The Issue Of Comprehension In InterculturalCommunication In Teaching Foreign Languages - Khazratova Zukhra Mamaraimovna (Euro Asian Journal Publishing, 2025)
A primary issue in intercultural communication is the comprehension, or more accurately, the miscomprehension between the involved parties. Cultural disparities contribute to misconceptions in intercultural communication. It is essential to comprehend the challenges that may emerge in intercultural communication and to actively strive to mitigate them. One must attentively observe the interlocutor's reactions and, upon noticing a response deemed inappropriate from our perspective, endeavor to discern its cause and adjust one's behavior and speech accordingly.
Keywords: Intercultural communication; community; foreign language